Comparative evaluation of geneXpert MTB/RIF assay and Ziehl-Neelsen staining for the diagnosis of tuberculosis - Hamal, Deependra; Shrestha, Rajani; Parajuli, Sulochana; Nayak, Niranjan; Bhatt, Dharm Raj; Subramanya, Supram Hosuru; Gokhale, Shishir (Journal of Kathmandu Medical College, 2022)
Background: Ziehl-Neelsen (ZN) staining for the diagnosis of tuberculosis is frequently used. Since ZN smear technique has poor sensitivity, molecular tool like GeneXpert assay have recently been introduced in Nepal. This study compared GeneXpert MTB/RIF assay with ZN stain microscopy for the diagnosis of tuberculosis.Objectives: To compare and evaluate GeneXpert MTB/RIF assay and Ziehl-Neelsen staining for the diagnosis of tuberculosis.Methods: An analytical observational study was conducted in Manipal Teaching Hospital, Pokhara from February 2020 to August 2021 after ethical clearance. A total of 355 clinical specimens (Sputum, Broncho-alveolar lavage, pus, lymph node aspirate etc) were collected and processed for Zeihl-Neelson staining and GeneXpert assay as per the recommended guidelines.Results: Zeihl-Neelson staining detected acid-fast bacilli (AFB) in 17 (4.78%) specimens, while GeneXpert assay showed positivity in 37 (10.42%). All the 17 smear positive sputum samples yielded positive result by GeneXpert also. AFB were not detected in any of the 318 samples negative by GeneXpert. Fifteen (83.3%) of the 18 specimens that showed high to medium density of bacilli by GeneXpert were positive by Ziehl-Neelsen staining. Only two (10.5%) of the 19 specimens with low bacillary density by GeneXpert were positive by Ziehl-Neelsen Staining. These differences were statistically significant (p